Production of cyathane type secondary metabolites by submerged cultures of Hericium erinaceus and evaluation of their antibacterial activity by direct bioautography. Issue 1 (December 2015) - Shen, T.; Morlock, G.; Zorn, H.
Abstract Background Fungi of the phylum Basidiomycota are well-known to form a broad spectrum of biologically active secondary metabolites, especially low molecular weight compounds such as terpenoids.Hericium erinaceus produces various cyathane type diterpenoids including erinacines. However, no quantitative data and production kinetics have been reported on the biosynthesis of the erinacines C and P in submerged cultures. In the present study, the production of erinacine C was optimized, and the product formation kinetics as well as the antimicrobial activity were studied by high-performance liquid chromatography (HPLC), high-performance thin-layer chromatography (HPTLC) and direct bioautography. Results Oatmeal and Edamin® K were identified to be crucial media components for an efficient production of erinacine C. The highest concentrations of erinacine C were obtained in the optimized culture medium on the 9th culture day (approximately 260 mg L−1 ). The production of erinacine P was strongly time dependent. The maximum concentration of erinacine P of 184 mg L−1 was observed on the third culture day. Afterwards, the concentrations of erinacine P decreased while the concentrations of erinacine C steadily increased. Comparable results were obtained by HPTLC with UV detection and HPLC with diode-array detection (DAD) analyses. Direct bioautography allowed for an additional analysis of the antimicrobial activity of the secondary metabolites. Conclusions The C and N sources oatmeal and Edamin® K induced the formation of erinacine C. Detailed product formation kinetics of the erinacines C and P have been reported for the first time. HPTLC combined with theAliivibrio fischeri bioassay allowed for an instant detection of cyathane diterpenoids in crude extracts and for an evaluation of the antimicrobial activity of the secondary metabolites directly on the plate.